Analysis of Sheikh Yusuf Al-Qardhawi's View on Ikhtilat from the Perspective of Sadd al-Zari’ah - Ahmad, Khairin; Safruddin Edi Wibowo; Mursalim, Mursalim (Eastasouth Institute, 2025)
This article examines Sheikh Yusuf Al-Qardhawi’s views on the concept of ikhtilat from the perspective of sadd al-zari’ah, a preventive principle in Islamic jurisprudence aimed at closing the doors to harm or damage. This study is qualitative in nature, employing a library research method within normative Islamic legal research, using a conceptual approach or an analysis of the scholar’s thought. The research is descriptive-analytical. The results reveal that, according to Yusuf Al-Qardhawi, the default ruling on gatherings between men and women (ikhtilat) is permissible. However, the ruling can vary depending on the surrounding circumstances. The permissibility of ikhtilat gatherings is also subject to several conditions, including: guarding one’s gaze, covering the aurat (parts of the body that should be covered), avoiding conspicuous appearance, preventing seclusion (khalwat), and limiting the gathering strictly to necessary purposes. Al-Qardhawi’s view on the permissibility of ikhtilat is based on the principle of sadd al-zari’ah.